MENINGKATAN MINAT DAN HASIL PEMBELAJARAN MATEMATIKA MATERI JENIS SUDUT MENGGUNAKAN METODE DISKUSI KELOMPOK SISWA KELAS III SDN 9 MELAI SEMESTER 2 TAHUN PELAJARAN 2018/2019 - Ratnawati, Ratnawati (JGK (Jurnal Guru Kita), 2020)
Abstract: Increasing Interest and Results of Mathematics Learning Angle Type Material Using Discussion Method of Third Grade Students Sdn 9 Melai Semester 2 Year Lesson 2018/2019. This research is based on the problem of low interest and learning outcomes of grade III students at SDN 9 Melai, especially on the math content, judging by the completed individual scores obtained results that from 36 sisw only 7 students (19.44%) who have reached KKM (70). This research uses the Class Action Research (PTK) method using two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subject of the study was grade III students of SDN 9 Melai which numbered 36 students. Data collection is carried out with student observation sheets, documentation and test results in each cycle. Furthermore, the data is analyzed by means of quantitative analysis and qualitative analysis. The results prove the use of group discussion methods can increase student interest showing gains in the initial study of 12 students or 33.33%, rising to 25 students or 69.44% in the first cycle, and 94.44% or 34 students in the second cycle. This was also supported by students’ learning outcomes from the average in the study of 55.83, rising to 66.94 in the first cycle, and 77.50 in the second cycle, with a level of learning completeness of 7 students (19.44%) in the initial study, 66.94% or 23 students in the first cycle, as well as 31 students or 86.11% in the second cycle and overall all learning success criteria have been achieved in the second cycle. The conclusion is that the use of group discussion methods can increase the interest and learning outcomes of grade III students of SDN 9 Melai Semester 2 year 2018/2019 on mathematics lessons of corner type material. Keywords: Interests, Learning Outcomes, Group Discussions Abstrak: Meningkatan Minat Dan Hasil Pembelajaran Matematika Materi Jenis Sudut Menggunakan Metode Diskusi Kelompok Siswa Kelas Iii Sdn 9 Melai Semester 2 Tahun Pelajaran 2018/2019. Penelitian ini dilatarbelakangi adany amasalah rendahnya minat dan hasil belajar siswa kelas III SDN 9 Melai khususnya pada muatan matematika, dilihat dari ketuntasan nilai individu diperoleh hasil bahwa dari 36 sisw ahanya 7 siswa (19,44%) yang telah mencapai KKM (70). Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan menggunakan dua siklus. Tiap siklus terdiri dari empat tahap yaitu perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian adalah siswa kelas III SDN 9 Melai yang berjumlah 36 siswa. Pengumpulan data dilakukan dengan lembar observasi siswa, dokumentasi serta tes hasil belajar di setiap siklusnya. Selanjutnya data dianalisis dengan cara analisis kuantitatif dan analisis kualitatif. Hasil penelitian membuktikan penggunaan metode diskusi kelompok dapat meningkatkan minat siswa menunjukkan perolehan pada studi awal 12 siswa atau 33,33%, naik menjadi 25 siswa atau 69,44% pada siklus pertama, dan 94,44% atau 34 siswa pada siklus kedua.Hal tersebut didukung pula oleh hasil belajar siswa dari rata-rata pada studi 55,83, naik menjadi 66,94 pada siklus pertama, dan 77,50 pada siklus kedua, dengan tingkat ketuntasan belajar sebanyak 7 siswa (19,44%) pada studi awal, 66,94% atau 23 siswa pada siklus pertama, serta 31 siswa atau 86,11% pada siklus kedua dan secara keseluruhan semua kriteria keberhasilan pembelajaran telah tercapai pada siklus kedua. Kesimpulannya adalah penggunaan metode diskusi kelompok dapat meningkatkan minat dan hasil belajar siswa kelas III SDN 9 Melai Semester 2 Tahun Pelajaran 2018/2019 pada pelajaran matematika materi jenis sudut. Kata Kunci : Minat, Hasil Belajar, Diskusi Kelompok